Quando canta a liberdade: a desinstitucionalização da mulher egressa do sistema prisional paulista - Garcia, Paula Paschoal Rodrigues (2019)
The present research starts from the scenario of the fast-increased number of incarcerated women in Brazil and the effects of punishment on the life of these women. The goal of this research was to understand the process of deinstitutionalization, which starts from the period of serving the sentence in deprivation of liberty, through the life experience of women who have been discharged from the Sao Paulo prison system and how they face this path. The methodology consisted of conducting interviews aided by guide-topics with four egressed women. The fieldwork also involved monitoring attendance with egressed individuals and their families, as well as informal conversations with members of non-profits and other social organizations. The research aimed to contribute to understand the mechanisms of institutional power, gender issues in the institutional and post-institutional reality, the effects of prison that permeate in and negotiations in freedom and the importance of public policies aimed at women. After the prison period, women developed strategies to deal with stigma and lack of support through different self-presentations, way they have conquered more space. The process towards freedom is presented as merely bureaucratic and “assistance” remains on the bias of punishment, contributing to the spread of prejudices. Other points that the analysis of the reality of the egressed women show is that their experiences are marked by precarious work, fragile bonds, lack of information and precarious access to rights and citizenship, all of which are aggravated due to prison experience.